The effects and the macroeconomic dynamics of natural disaster damages: investigation of local evidence - Agim Kukeli (Regional Studies, Regional Science)
This study investigates the macroeconomic consequences of natural disasters in southeast Texas, a region frequently distressed by meteorological and hydrological events. By concentrating on a county-level analysis, we methodically assess the impacts of natural disaster damages on key economic indicators: aggregate personal income, aggregate wages, wages per worker, aggregate employment and aggregate income transfers over the period 1990–2019. In addition, using the panel vector autoregression (PVAR) model, the research examines the complex dynamics between these economic variables under the stress of natural disaster shocks, offering a better understanding of their interplay and evolution over time. Findings reveal that natural disasters cause a noteworthy influence on the regional economy, with more than four events annually leading to an average loss equivalent to 2.2% of the region's real personal income. The study finds that natural disaster damages adversely affect wages and unemployment but do improve real personal income and real income transfer. The analysis also sheds light on their extended economic effects, thereby enhancing understanding of the resilience and adaptive mechanisms at play within affected communities. This study's unique contribution lies in its detailed examination of southeast Texas's economic resilience and vulnerability, which provides invaluable insights into the macroeconomic dynamics of natural disaster damages. The use of PVAR methodology enables a sophisticated analysis of the causal relationships and temporal dynamics, paving the way for informed policymaking to mitigate the adverse impacts of future natural disasters.